Reentry and transition into college life: A study of formerly incarcerated individuals in Southern California. - Anderson, Annika; Fox, Roberta; Jones, Paul; Joseph, Rigaud; Witherell, Wendi; Adams, Ashley (Journal of Human Behavior in the Social Environment, 2024)
In California, formerly incarcerated individuals face several challenges while pursuing higher education. To combat these challenges, there are several programs in the California higher education system that provide supportive services for formerly incarcerated college students (FICS). Yet, there have been limited scholarly evaluations of the efficacy of these programs for formerly incarcerated individuals. This study uses a mixed-methods design to fill this gap in the literature and pursue its threefold purpose: (1) investigate how formerly incarcerated college students (FICS) describe their transition into college life, (2) determine the characteristics of a successful campus-based reentry program for system-impacted students, and (3) explore the extent to which existing campus support programs have addressed their needs. Interviews conducted with 18 FICS (N = 18) reveal that FICS would benefit from a broad range of campus services—with academic, technological, financial, work, legal, and human connection components. Meanwhile, descriptive statistics show that (a) campus support programs make more than two-thirds of FICS feel welcome and (b) about a third of the study participants experienced a smooth transition into college life. These findings support reentry programs like Project Rebound and suggest a need for individual case management as well as cross-campus and community collaboration.